The Flash. The complete eighth season [videorecording (DVD)] - Berlanti, Greg; Kreisberg, Andrew, 1971-; Johns, Geoff, 1973- (Warner Bros. Entertainment Inc., 2022)
After defeating Godspeed with the help of his speedster children from the future, Bart and Nora, Barry Allen aka The Flash are back to face new challenges in Season Eight. With the help of Team Flash at STAR Labs Caitlyn Snow/Killer Frost, Allegra Garcia, Chester P. Runk and his family journalist wife Iris West-Allen, Joe West, and Cecile Horton The Flash will face villains old and new in Central City. Season Eight begins with an epic five-episode event, 'Armageddon' featuring crossover characters from across the Arrowverse.